Manajemen Pengelolaan Wakaf : Studi Kasus pada Lembaga Tabung Wakaf Indonesia - Fernando Yusuf; Moh Mukhsin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
According to the term, waqf is the holding of assets whose benefits are taken without being destroyed immediately for permissible use and is intended to obtain the blessing of Allah SWT. This study aims to analyze the management of waqf at the Indonesian Waqf Tabung institution in the waqf fund model and the programs implemented with benefits to various fields. This research uses qualitative research methods. The data used consists of primary data and secondary data obtained through observation and pre-existing literature or research. The research results show that the waqf management at Tabung Waqf Indonesia is in accordance with Islamic law, can run programs well and is invested in various forms of business with surplus proceeds being used for social programs, and the management of the waqf has had positive implications in improving the community's economy. This research contributes to the development of studies related to waqf management at the Indonesian Tabung Waqf institution in the waqf fund model and the programs implemented with a more detailed explanation along with their relationship to benefits in the fields of health, education, economics and social development.